Panji, Karya Nusantara yang Mendunia: Suatu Kajian Folklor Tentang Keberterimaan “Barang” Impor - Ery Soedewo (Berkala Arkeologi Sangkhakala, 2009)
AbstractPanji story is one of creativity form from ancient Java periode that’s still enjoyed till now in many representation forms. The spread of it not only in South-East Asia archipelago but also to South- East Asia mainland. The similarity of some autochton elements made the story could be accepted in anyplace